Sociocultural Sustainability of Small Tourism Enterprises: Observations from Ghalegaon’s Community Based Homestays - Acharya, Baikuntha Prasad; Halpenny, Elizabeth (Journal of Tourism and Hospitality Education, 2017)
Ghalegaon represents one of Nepal’s most popular rural community based tourism entrepreneurship initiatives in a form of home stays. This paper explores the socio cultural sustainability of the Ghalegaon home stays. Fourteen individual interviews, five focus group discussions and onsite observations were used to discuss four categories of socio cultural dimension of sustainability: 1) inclusive, 2) collaborative, 3) resilient, and 4) modernizing. The findings revealed a slow impact of tourism with variations in perceptions of the local people. A critical insight to respective stakeholders are offered. Journal of Tourism and Hospitality Education Vol. 7, 2017